Performance analysis of superheated steam injection for heavy oil recovery and modeling of wellbore heat efficiency. (15th April 2017) - Sun, Fengrui; Yao, Yuedong; Chen, Mingqiang; Li, Xiangfang; Zhao, Lin; Meng, Ye; Sun, Zheng; Zhang, Tao; Feng, Dong
Abstract: In this paper, a novel model is proposed for predicting thermo-physical properties of superheated steam (SHS) in SHS injection wells and for estimating wellbore heat efficiency. Firstly, a novel mathematical model is proposed for predicting pressure, temperature as well as superheat degree in SHS injection wells. Secondly, the direct and indirect methods are introduced to estimate the wellbore heat efficiency. Thirdly, the model solving process is introduced in detail. After validation of the model, sensitivity analysis is conducted. Results indicate that: (1). The superheat degree at well bottom increases with the increase of injection rate. (2). The superheat degree at well bottom increases with the increase of injection temperature. (3). The superheat degree at well bottom decreases with the increase of injection pressure. In order to obtain a higher superheat degree at well bottom, the injection pressure cannot be too high. This paper presents a basic reference for engineers in optimization of injection parameters as well as estimation of wellbore heat efficiency of SHS injection wells. Highlights: Wellbore modeling becomes a hot spot in the thermal recovery engineering. A novel model is proposed to predict the thermal parameters of SHS in the wellbores. An improved analytical model is introduced for estimating wellbore heat efficiency. Type curves of SHS flow in the wellbores are obtained by finite difference method. The effect of injection parameters on superheat degree are studied in detail.